Turning 21: Induction of miR-21 as a Key Switch in the Inflammatory Response - Sheedy, Frederick J. (Frontiers in Immunology, 2015)
miR-21 is one of the most highly expressed members of the small non-coding microRNA family in many mammalian cell types. Its expression is further enhanced in many diseased states including solid tumors, cardiac injury and inflamed tissue. Whilst the induction of miR-21 by inflammatory stimuli cells has been well documented in both hematopoietic cells of the immune system (particularly monocytes/macrophages but also dendritic and T-cells) and non-hematopoietic tumorigenic cells, the exact functional outcome of this elevated miR-21 is less obvious. Recent studies have confirmed a key role for miR-21 in the resolution of inflammation and in negatively regulating the proinflammatory response induced by many of the same stimuli that trigger miR-21 induction itself. In particular, miR-21 has emerged as a key mediator of the anti-inflammatory response in macrophages. This suggests that miR-21 inhibition in leukocytes will promote inflammation and may enhance current therapies for defective immune responses such as cancer, mycobacterial vaccines or Th2-associated allergic inflammation. At the same time, miR-21 has been shown to promote inflammatory mediators in non-hematopoietic cells resulting in neoplastic transformation. This review will focus on functional studies of miR-21 during inflammation which are complicated by the numerous molecular targets and processes that have emerged as miR-21 sensitive. It may be that the exact functional outcome of miR-21 is determined by multiple features including the cell type affected, the inducing signal, the transcriptomic profile of the cell, which ultimately affect the availability and ability to engage different target mRNAs and bring about its unique responses. Reviewing this data may illustrate that RNA-based oligonucleotide therapies for different diseases based upon miR-21 may have to target the unique and operative miRNA:mRNA interactions functionally active disease.